Why the Lower-membered Alkanoic Acids are Infinitely Soluble in Water whereas the Higher-membered Ones have a Very Low Solubility in Water? A Molecular Modeling Analysis - Huq, Fazlul (Asian Journal of Chemistry, 2016)
Molecular mechanics, semi-empirical and density function theory (DFT) calculations using HyperChem 7 and Sparta’02 were carried out to investigate whether the results obtained can explain the decrease in solubility in water of alkanoic acids with the increase in carbon chain length. Semi-empirical calculations using HyperChem 7 according to AM1 procedure show that for methanoic acid, ethanoic, propanoic acid and butanoic acid, the energy of hydration is indeed greater in magnitude than the heat of evaporation so that there is a net release of heat energy as the compounds go in solution in water. A decrease in enthalpy and an increase in entropy mean that the change in Gibb’s free energy is negative so that solubility equilibrium cannot be established for the compounds. For the higher-membered alkanoic acids, the calculated energy of hydration is found to be less in magnitude that the heat of evaporation so that solubility equilibrium is established for the compounds. Although PM3 calculations provide a better estimate of heat of formation in the gaseous state, it is found that the calculations generally underestimate the energy of hydration.